(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The process of student adaptation to professional-pedagogical activity represents a crucial phase in the development of future educators. This research delves into the multifaceted pedagogical aspects associated with facilitating and enhancing the adaptation of students to the complex realm of professional teaching roles. The study scrutinizes the challenges, strategies, and key pedagogical interventions essential for fostering successful adaptation to the demands and intricacies of the educational sphere. Drawing upon a synthesis of theoretical frameworks in pedagogy and educational psychology, this investigation elucidates the pivotal role played by educational institutions, educators, and the curriculum in shaping the adaptation process. It investigates the psychosocial and academic challenges encountered by students transitioning into pedagogical roles and examines how pedagogical strategies can effectively mitigate these challenges.